Scarcity and Abundance: An Ethical Framework in Islamic Economics Perspective - Muhammad Zulfikar Yusuf (Faculty of Islamic Economics and Business, State Islamic University of Kiai Haji Achmad Siddiq Jember, Indonesia, 2025)
Scarcity is the main discussion in economics. However, there has yet to be an agreed consensus in defining the concepts of scarcity and abundance, especially from an Islamic perspective. Even though the concept of scarcity is still an ongoing debate in Islamic economic discourse, there are other more essential discussion aspects of Islamic economics besides scarcity, namely moral ethics in dealing with scarcity and abundance. Because normatively, the Qur'an discusses the concepts of scarcity and abundance in many verses. Islamic economists see that by prioritizing a moderate attitude, Islamic economics can be directed to a more contributing perspective. Therefore, this paper attempts to fill this gap by offering an ethical framework for addressing the challenges of scarcity and abundance by being moderate. This conceptual paper explores an ethical framework for addressing the issue of moderate scarcity and abundance from an Islamic perspective. Employing text analysis from verses of the Qur'an and various Islamic economic literatures, the study reveals that the Qur'an provides a comprehensive ethical framework regarding scarcity and abundance, considering them not as absolute concepts. The paper emphasizes the importance of moderate Islamic ethics in responding to resource scarcity and abundance, aligning with the Qur'an's emphasis on balance and justice. The findings of this paper contribute to the ethical discourse on scarcity and abundance, highlighting the significance of moderation in dealing with these issues. The paper’s originality lies in presenting an ethical framework rooted in Qur'anic verses to address the matter of scarcity and abundance by being moderate.